PERTANGGUNGJAWABAN PENYIDIK KEPOLISIAN REPUBLIK INDONESIA DALAM TINDAKAN PENANGKAPAN TANPA ADANYA SURAT PERINTAH PENANGKAPAN - Dian Rahma Yunelfi; Emilda Firdaus; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Arrests carried out in the absence of an arrest warrant made by police investigators constitute acts contrary to the law which have been explained how to implement them in the Criminal Procedure Code, especially in Article 18 and are also regulated in the Regulation of the Head of the Indonesian National Police Number 6 Year 2019 concerning Criminal Investigations. Many cases of arrests without an arrest warrant can lead to arbitrary treatment by law enforcement and cause legal uncertainty for victims or suspects.This type of research can be classified as a type of normative legal research which specifically discusses the principles of law that are carried out on the legal norms which constitute a standard of behavior or attitude.The results of the research conducted by the author are that police investigators must be held liable for criminal liability because they have made mistakes in conducting the investigation process which will refer to professionalism as law enforcement. And also can provide legal certainty for victims and their families. The mistakes made by the police investigator should be justified as they should be not only in the form of apologies but also compensation and various sanctions that can be given to him.Keywords: Responsibility-Investigator-Arrest without a warrant